2018
DOI: 10.1002/pon.4649
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals' perspective on return to work in cancer survivors

Abstract: The training of professionals should increase awareness of the assumptions they make about cancer survivors in regard to RTW. Additionally, training might elaborate professionals' view of their role in the interaction with cancer survivors regarding RTW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Confusion over which member of the healthcare team is responsible for addressing employment may serve as a barrier to addressing these issues as part of care delivery. There may also be differences by discipline in how providers view their role in addressing employment issues and concerns (22).…”
Section: Healthcare Providers and Delivery System Level Gaps And Research Recommendations (Box 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Confusion over which member of the healthcare team is responsible for addressing employment may serve as a barrier to addressing these issues as part of care delivery. There may also be differences by discipline in how providers view their role in addressing employment issues and concerns (22).…”
Section: Healthcare Providers and Delivery System Level Gaps And Research Recommendations (Box 2)mentioning
confidence: 99%
“…. It is also widely accepted that a survivor's job performance, satisfaction, and engagement prior to cancer diagnosis are important drivers of work outcomes after cancer (22). However, few studies have examined these relationships and their impact on employment and job performance.…”
mentioning
confidence: 99%
“…OHNs are the frontline staff among occupational health professionals and if OHNs can be the good healthcare providers to the workers with cancer, the resignation rate can decrease. One of the important challenges toward the future should be to strengthen the collaboration among multi‐institutions and multiprofessionals including occupational health nursing professionals. Recently, Stone et al reported that interaction processes between cancer survivors and occupational and environmental health professionals comprised revealing the survivor‐self, sustaining workability, gatekeeping (employment opportunities and RTW), and accessing support.…”
Section: Discussionmentioning
confidence: 99%
“…The ethical review board of the School of Health Sciences in Tokai University approved this study (no. [11][12][13][14][15][16]. Along with the questionnaire, written explanations of the study objectives and ethical considerations, which include information about voluntary cooperation with no penalty for not responding to a questionnaire, anonymous response, and guaranteed privacy, were sent to the OHNs.…”
Section: Ethical Considerationmentioning
confidence: 99%
“…The importance of the healthcare professional roles has been investigated from the hospital-and workplace-based standpoints [15][16][17] . Yagil et al 16) reported studies that conducted inter views using questionnaires on specialties, showing that social workers and psychologists jointly discussed options and implications with the cancer sur vivor, while physicians and nurses provided information and suggestions. In a qualitative study, Stone et al.…”
mentioning
confidence: 99%